Masters Students' Perceptions of Distance and Transport Options - Mirjam Harkestad Olsen; Hermína Gunnþórsdóttir (Education in the North, 2018)
This article is situated within the Arctic Regions North Norway and North/East Iceland. It presents a study on what motivates adults in Arctic regions to apply for and complete a Master’s degree in Education. Motivation is examined in relation to distance, transport options and degree completion times, focusing on whether distance and transport options were significant motivation factors for students in the Arctic regions. Data is based around two Master’s degree programmes, one at the University of Akureyri in Iceland and the other in Alta, at the Arctic University of Norway. All students who had completed the Master’s degree programme in Akureyri and Alta respectively were invited to take part in a questionnaire distributed to students’ email addresses. The results are introduced in terms of distance and travel time and the reason for choice of university. The findings indicate that difficult weather conditions do not negatively affect students’ learning processes as the students seem rather to take these conditions and circumstances for granted. The students are driven by intrinsic motivation such as determination, relatedness and coping and their motivation is thus directed by ownership of the decision; a significant decision that also affects their partner and their children.